2000
DOI: 10.1002/1097-0134(20000901)40:4<613::aid-prot60>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional properties of a Bacillus subtilis temperature‐sensitive σA factor

Abstract: Bacillus subtilis DB1005 is a temperature-sensitive (Ts) sigA mutant containing double-amino-acid substitutions (I198A and I202A) on the hydrophobic face of the promoter -10 binding helix of sigma(A) factor. We have analyzed the structural and functional properties of this mutant sigma(A) factor both in vivo and in vitro. Our data revealed that the Ts sigma(A) factor possessed predominantly a multimeric structure which was prone to aggregation at restrictive temperature. The extensive aggregation of the Ts sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The dispensability of this region for B. subtilis A to function (Fig. 2, 3, 5, and 6) implies that it can be independent and separated from other domains of further support also comes from our previous study, in which Arg-103 was shown to be more accessible to trypsin digestion (34). It has been proposed that the acidic region 1.1 of Taq A localizes directly inside the main channel and interacts with the basic surface of the channel wall of the RNA polymerase core enzyme (23).…”
Section: Discussionsupporting
confidence: 64%
“…The dispensability of this region for B. subtilis A to function (Fig. 2, 3, 5, and 6) implies that it can be independent and separated from other domains of further support also comes from our previous study, in which Arg-103 was shown to be more accessible to trypsin digestion (34). It has been proposed that the acidic region 1.1 of Taq A localizes directly inside the main channel and interacts with the basic surface of the channel wall of the RNA polymerase core enzyme (23).…”
Section: Discussionsupporting
confidence: 64%
“…2) is quite different from that observed for the Ts sigA mutant (B. subtilis DB1005) with Ile-198, 202-Ala substitutions on the hydrophobic face of the promoter -10 binding helix of cr*, of which the growth potential is comparable to that of the Wt at 37°C (12). We speculated that the replacement with alanine of the bulky hydrophobic amino acid on the second helix of region 2.1 had affected the structure of cr* differently from the reported effect of the Ile-to-Ala substitution in region 2.4 of cr* (13).…”
Section: Construction and Growth Potential Of The B Subtilis Sigamentioning
confidence: 88%
“…3). With G3b promoter as DNA template, the relative activity of RNA polymerase containing the Wt-, L145A-, I149A-, or Y^A-cr* was in the ratio of L145A, I149A, and Y153A Cause Structural Instability of a^ Even at 37°C-The decreased transcription activity of a mutant a factor may be attributed to structural instability (38)(39)(40), aggregation of folding intermediate (13), or low core-binding activity of the mutant cr factor (17,(24)(25). It could also be a result of low promoter-binding activity, change in promoter specificity (5,(9)(10)(11), blocking of transcription initiation (41), or defective open complex formation of the mutant cr-containing RNA polymerase (42,43).…”
Section: Construction and Growth Potential Of The B Subtilis Sigamentioning
confidence: 99%
See 2 more Smart Citations